ANALISIS STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MENENGAH TAHU DALAM UPAYA PENINGKATAN PENDAPATAN DI DESA KARYA MAKMUR KECAMATAN MADANG SUKU III KABUPATEN OKU TIMUR - Yanti, Priska Dama; Rosmawati, Henny; Lastinawati, Endang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The purpose of this study is to analyze the strategy for developing tofu micro, small and medium enterprises in an effort to increase income in Karya Makmur Village, Madang Suku III District, East Oku Regency and to find out the obstacles that affect increased production and the strategies used in efforts to increase income. This research was conducted using descriptive qualitative research methods with Milles and Huberman data analysis models. Data was collected through a series of observations and interviews conducted directly with the parties involved in the research. The results showed that the obstacles faced in the development of tofu SMEs in an effort to increase production were raw materials such as rising soybean prices and obstacles to auxiliary materials, namely cooking oil and wood, besides that marketing was still on a small scale and limited capital. The strategy used for business development carried out by industry players, umkm tofu in Karya Makmur Village, in an effort to increase income is to improve marketing strategies and use production technology to improve product quality.